Hegemoni Ideologi dalam Novel Ayat-Ayat Cinta Karya Habiburrahman el Shirazy (Kajian Hegemoni Gramsci) - Fajrul Falah (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Research on the novel Ayat-Ayat Cinta (AAC) by Habiburrahman el Shirazy with ideological hegemony approach, the author's knowledge based on search on the internet, reference to the latest online journal (last 5 years), not found yet. Various related studies AAC most of them reviewed from the aspect of religiosity, da'wah and religious messages. This study aims to reveal ideological hegemony contained in the novel AAC. This literature study research, using the Gramsci hegemony approach. The research method used is descriptive analytic. The results showed Fahri's main character was constructed by the author with many positive attributes attached; handsome, smart, simple, obedient, and kind. These positive attributes and images make most female figures (Aisha, Maria, Nurul, Noura, Alicea) interested and admired Fahri, so Fahri also benefited and became a dominant class (hegemonic). Hegemony process these figures pan out, because one of them supported by religious ideology.